Reported appetite, taste and smell changes following Roux-en-Y gastric bypass and sleeve gastrectomy: Effect of gender, type 2 diabetes and relationship to post-operative weight loss. (1st December 2016) - Makaronidis, Janine M.; Neilson, Sabrina; Cheung, Wui-Hang; Tymoszuk, Urszula; Pucci, Andrea; Finer, Nicholas; Doyle, Jacqueline; Hashemi, Majid; Elkalaawy, Mohamed; Adamo, Marco; Jenkinson, Andrew; Batterham, Rachel L.
Abstract: Reduced energy intake drives weight loss following Roux-en-Y gastric bypass (RYGB) and sleeve gastrectomy (SG) procedures. Post-operative changes in subjective appetite, taste, and smell and food preferences are reported and suggested to contribute to reduced energy intake. We aimed to investigate the prevalence of these changes following RYGB and SG and to evaluate their relationship with weight loss. 98 patients post-RYGB and 155 post-SG from a single bariatric centre were recruited to a cross-sectional study. Participants completed a questionnaire, previously utilised in post-operative bariatric patients, to assess the prevalence of post-operative food aversions and subjective changes in appetite, taste and smell. Anthropometric data were collected and percentage weight loss (%WL) was calculated. The relationship between food aversions, changes in appetite, taste and smell and %WL was assessed. The influence of time post-surgery, gender and type 2 diabetes (T2D) were evaluated. Following RYGB and SG the majority of patients reported food aversions (RYGB = 62%, SG = 59%), appetite changes (RYGB = 91%, SG = 91%) and taste changes (RYGB = 64%, SG = 59%). Smell changes were more common post-RYGB than post-SG (RYGB = 41%, SG = 28%, p = 0.039). No temporal effect was observed post-RYGB. In contrast, the prevalence of appetite changes decreased significantly with time following SG. Post-operative appetite changes associated with and predicted higher %WL post-SG but not post-RYGB. Taste changes associated with and predicted higher %WL following RYGB but not post-SG. There was no gender effect post-RYGB. Post-SG taste changes were less common in males (female = 65%, males = 40%, p = 0.008). T2D status in females did not influence post-operative subjective changes. However, in males with T2D, taste changes were less common post-SG than post-RYGB together with lower %WL (RYGB = 27.5 ± 2.7, SG = 14.6 ± 2.1, p = 0.003). Further research is warranted to define the biology underlying these differences and to individualise treatments.